The three axial ages : moral, material, mental - Torpey, John, 1959- (Rutgers University Press, 2017)
"How should we think about the "shape" of human history since the birth of cities, and where are we headed? Sociologist and historian John Torpey proposes that the "Axial Age" of the first millennium BCE, when some of the world's major religious and intellectual developments first emerged, was only one of three such decisive periods that can be used to directly affect present social problems, from economic inequality to ecological destruction. Torpey's argument advances the idea that there are in fact three "Axial Ages," instead of one original Axial Age and several subsequent, smaller developments. Each of the three ages contributed decisively to how humanity lives, and the difficulties it faces. The earliest, or original, Axial Age was a moral one; the second was material, and revolved around the creation and use of physical objects; and the third is chiefly mental, and focused on the technological. While there are profound risks and challenges, Torpey shows how a worldview that combines the strengths of all three ages has the potential to usher in a period of exceptional human freedom and possibility"--